Assentamentos urbanos sustentáveis : contribuições internacionais e nacionais pela busca do direito fundamental à moradia digna no Município de Santos - Mateus, Douglas Predo (2017)
The work analyses local governments participations in the formulation of politics and actions referring to deserving habitation in according to international documents like, ¿Habitat Agenda¿ and ¿New Urban Agenda¿, came from Habitat Meeting. In the context of International Environment Law Program tries answer the question: ¿Can local governments do the environment international urban law?¿ From a study developped in Santos, SP between 1993 e 1996, triess to discuss how this participation occurs, if objectifying adapt to international documents, or looking for international problems solutions, to this uses hypotheic-deductive methodology and organizes into four chapters, which includes international documents that established and discuss deserving habitation, historic contexto and the national legislation that cares this question, the participation of the State and the Market, the Global Environment Governance and the study about Santos Municipality. This work proposes to use ¿Habitat Agenda¿ how a methodology of insert the State participation to warrant citizenship, rights to habitation, to the city, democratization and descentralization of State.